2009
DOI: 10.1007/s10453-009-9116-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of birch airborne pollen counts by examining male catkin numbers in Hokkaido, northern Japan

Abstract: Birch pollen is a very common cause of pollinosis in Hokkaido, northern Japan. Birch airborne pollen concentrations vary each year; hence, the development of a method for predicting annual airborne pollen concentration is very important in preventing widespread symptoms of pollinosis. In the current study, we investigated airborne pollen counts and male catkin numbers (male flower index) of birch in four cities of Hokkaido between 2002 and 2008. Airborne pollen surveys were conducted using Durham's sampler, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…During 1999 and 2005, the weather conditions did not differ much from the 15-year-mean. The rain episodes during the pollen season, which were suggested by Ranta et al (2008) and Yasaka et al (2009) as being potentially responsible for reducing SPI, were not common in Poznań during the examined period (e.g. only three rainy days during 2005 pollen season).…”
Section: Characteristic Of Pollen Season/meteorological Parameters (Mp)mentioning
confidence: 86%
“…During 1999 and 2005, the weather conditions did not differ much from the 15-year-mean. The rain episodes during the pollen season, which were suggested by Ranta et al (2008) and Yasaka et al (2009) as being potentially responsible for reducing SPI, were not common in Poznań during the examined period (e.g. only three rainy days during 2005 pollen season).…”
Section: Characteristic Of Pollen Season/meteorological Parameters (Mp)mentioning
confidence: 86%
“…The daily pollen amount was more predictable in abundant years of 2004,2006,2008,2010, and 2011, while it was less predictable in poor-yield years of 2003, 2007 and 2009. Hence, combined with a prediction for annual-sum pollen amount established by Yasaka et al (2009), the statistical method that we proposed in this paper could be utilized in a practical application to the short-term pollen prediction during the flowering season.…”
Section: Resultsmentioning
confidence: 99%
“…Kobayashi et al (2014) analyzed the data and revealed that the amount of the annual birch pollen varied with a significant biennial rhythm and gradually increased. Yasaka et al (2009) moreover paid attention to a high correlation between the male catkin number in a year and the pollen amount in the following year (Ranta et al 2008), and developed a practical prediction method for annual-sum pollen amount. This method is actually helpful for the prescription of pollen prophylactics before the pollen season.…”
Section: Introductionmentioning
confidence: 99%
“…This assumption seems to be particularly important when the tree distribution is scattered. A scattered tree distribution causes the unconstrained development of branches, foliage and inflorescences and, therefore, results in a higher pollen production [78]. The birch trees growing at lower densities can increase the crown size up to two times compared to that of the trees growing in dense forests [79].…”
Section: Vertical Dimension Of the Pollen Inventory-the Use Of Lidar mentioning
confidence: 99%
“…The assumption that crown surface is a predictor of pollen emission can also be biased by different numbers of catkins on trees of the same size. Ranta et al [10] and Yasaka et al [78] estimated that the number of catkins varies between years, which impacts the airborne pollen count. This variation implies that the crown surface may not be the only predictor of pollen emission, but it must be combined with other variables, such as phenological or meteorological data, that can explain the year-to-year variation in pollen count [84].…”
Section: Limitations Of the Study And Future Workmentioning
confidence: 99%